Estimating a New Zealand NAIRU - Kam Leong Szeto; Melody Guy (New Zealand Government, The Treasury, 2004)
This paper estimates the non-increasing inflation rate of unemployment or NAIRU for New Zealand. A NAIRU that varies over time has important implications in considering inflationary pressures. This paper estimates the time-varying NAIRU using a Kalman filter on a reduced form approach and extends previous studies in several ways. Using different model specifications and dependent variables suggests a band of NAIRU estimates of between four and five percent (with further error bands around that). The results of this paper indicate that the NAIRU is a relevant concept and the unemployment gap should be one of the factors considered when assessing inflationary pressure.
Keywords: E24; E31; C13; C22; 330; NAIRU; Kalman filter; Unemployment; Phillips Curve; New Zealand